Balancing development and forest environmental management through legal mechanism based on Naqli and Aqli / Adzidah Yaakob - Yaakob, Adzidah (2014)
This paper seeks to examine possible legal mechanism and environmental law principles that based on the integration of naqli and aqli. Current legal approach especially towards forest environment is seen to be ineffective when the forested areas in Peninsular Malaysia drastically reduce over the years and continues to decline even now. As in 2012, there were 5.79 million ha or 43.9% of forested land in Peninsular Malaysia. Out of this, 37.1% or 4.89 million ha were gazetted as Permanent Reserve Forest (PRF) or Permanent Forest Estate (PFE) and under the management of the Department of Forestry. The PRF or PFE can be easily excised from the gazette under the provisions of the National Forestry Act 1984 (NFA). Degazettement or excision of forest reserve areas is done mainly for the purpose of boosting economy as well as generating revenue for the state i.e. forest clearing for agriculture, the development of new town areas, a luxury residential area and also the industrial area. Therefore, a legal mechanism and environmental law principles that based on the integration of naqli and aqli is seen as a holistic approach in anticipating balance in economic development and forest environment.